Pediatric incontinence questionnaire (PINQ): translation and transcultural adaptation to Brazilian Portuguese - Rita Pavione Rodrigues Pereira; Angélica Quintino Leitão; Gabriella Silva Fotakos; Joceara Neves dos Reis; Flávio Eduardo Trigo Rocha; Marcos Giannetti Machado; Wendy F. Bower; Clarice Tanaka (Elsevier, 2023)
Objective: Lower urinary tract symptoms (LUTS) affect approximately 10% of children worldwide and are related to psychosocial manifestations and compromised quality of life, both for children and their families. The assessment of emotional conditions of LUTS in children is recommended by International Children's Continence Society; however, there is no specific instrument in the Brazilian Portuguese language. Therefore, the aim of this study was to translate, culturally adapt and assess the internal consistency of the Brazilian Portuguese version of the Pediatric Incontinence Questionnaire (PINQ). Material and methods: This cross-sectional study was performed at two referral centers for childhood voiding dysfunction. The 20-item PINQ was translated into Brazilian Portuguese and culturally adapted according to Beaton, 2000. His-standard methodology consists of 6 phases: translation, synthesis, back-translation, expert committee, and pre-test. The internal consistency was assessed using Cronbach's alpha. Results: The PINQ-br version was developed, validated by a committee of experts, and pre-tested on 44 children diagnosed with lower urinary tract symptoms, 23 boys and 21 girls (mean age: 9.7 and 9.6 years old respectively), as well as on their parents. The internal consistency was considered satisfactory, reaching Cronbach's alpha coefficient of 0.74 when applied to children and 0.82 when applied to parents. Conclusions: The PINQ was translated and culturally adapted to Brazilian Portuguese to assess the impact of LUTS on the health-related quality of life in Brazilian children and adolescents.